Teleworking and Congestion: A Dynamic Bottleneck Analysis - Sergejs Gubins; Erik T. Verhoef (Tinbergen Institute, 2011)
We analyze the welfare effects of part-day teleworking on road traffic congestion in the context of Vickrey's dynamic bottleneck model. Endogenous decisions to become equipped with a teleworking-enabling technology change the scheduling of arrival times at work for equipped drivers and, due to congestion externalities, affects travel costs of all drivers. We show that even costless teleworking might be marginally welfare reducing, after reaching the optimal penetration level, as an equipped driver imposes a higher travel externality on other equipped drivers than unequipped drivers do. We study various possible market configurations for the supply of the technology, and find that private monopolistic supply of the technology might yield a higher social welfare than perfectly competitive supply.
urn:NBN:nl:ui:31-1871/38573
Keywords: D62; O33; R41; R48; 330; traffic congestion; teleworking; bottleneck model; Verkehrsstau; Telearbeit; Bottleneck; Wohlfahrtsanalyse